Strategic Stability and Cyber Warfare: Challenges and Implications - Mr. Majid Mahmood (CISS Insight Journal, 2014)
Deterrence continues to be an important feature of international political life regardless of the conditions of polarity in the international system. The origin of strategic stability concept can be traced back to the Cold War deterrence configuration in the bi-polar relations of two nuclear armed super powers in terms of Mutually Assured Destruction or MAD. MAD implied that the correlations of nuclear forces are such that it discourages first strike thereby preserving the mutual vulnerability of the physical state. Thus nuclear deterrence is the core concept upon which the foundation of strategic stability is built or at least sought by states. It is important to mention that deterrence in isolation is a fragile basis of strategic thinking and it should be placed within broader framework of policy objectives. Nuclear armed states have an interest in preserving their nuclear capabilities against a number of contingencies that can potentially erode their nuclear potential. The challenge to deterrence and strategic stability is to be analyzed in the traditional framework of analysis. Cyber domain is increasingly becoming a major concern in regards to warfare in general and strategic stability in particular. However, it is a complex phenomenon and the complexity emanates from factors such as varying magnitude of network attacks and its impact, problem of attribution, varying doctrinal perceptions among states and proportionality and nature of responses.